1983
DOI: 10.1001/archotol.1983.00800260049012
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Adenocarcinoma of Minor Salivary Gland Origin in a Child

Abstract: \s=b\A papillary adenocarcinoma with metastasis occurred in a 5-year-old child. The neoplasm arose on the anterolateral sublingual aspect of the tongue and metastasized to a submandibular lymph node. Histologically, the tumor contained broad glandular papillary projections. The tumor cells were cuboidal and had vesicular, "ground glass" nuclei. Colloidlike material was found within the stroma and lumen of the glands. To determine whether the papillary adenocarcinoma was of minor salivary gland or ectopic thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…reported a tumour of the tongue in a 59‐year old man which was called ‘tubular adenocarcinoma’, 20 and Crocker et al . described a 5‐year‐old boy with an adenocarcinoma, which they called ‘papillary adenocarcinoma of minor salivary gland’ 21 . Even allowing for the difficulties of proper assessment of figures in reprints, there are many similarities to the microscopic appearance of our cases.…”
Section: Discussionmentioning
confidence: 74%
“…reported a tumour of the tongue in a 59‐year old man which was called ‘tubular adenocarcinoma’, 20 and Crocker et al . described a 5‐year‐old boy with an adenocarcinoma, which they called ‘papillary adenocarcinoma of minor salivary gland’ 21 . Even allowing for the difficulties of proper assessment of figures in reprints, there are many similarities to the microscopic appearance of our cases.…”
Section: Discussionmentioning
confidence: 74%
“…Both tumors were highly differentiated cysladcnocarcinomas with mucus production. The youngest patient with an adenocarci noma was a 5-ycar-old boy with a tumor in the sublingual glands [10], Epidermoid carcinomas in children are rare [1.5. 22], We observed 2 cases of mod erately differentiated squamous cell carcino mas metastasizing to lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Even allowing for the difficulties of proper assessment of figures in reprints, there are many similarities to the microscopic appearance of our cases. Particularly reminiscent are the pallor and ground glass quality of the nuclei as seen in both tumors, the solid and cribriform arrangement in the first tumor [18] and the papillary appearance resulting from tumor cell detachment from the stroma as seen in the other report [19]. As a consequence therefore, we strongly suspect that if cases of CATMSG were to be excluded from the figures for PLGA, then the metastatic rate of true PLGA would be much lower.…”
Section: Differential Diagnosismentioning
confidence: 94%
“…Two other possible candidates for CATMSG were published under different names, and both carcinomas metastasized to the cervical lymph nodes. Yajima et al [18] reported a tumor of the tongue in a 59-year old man which was called ''tubular adenocarcinoma'', and Crocker et al [19] described a 5-year-old boy with an adenocarcinoma, which the authors designated ''papillary adenocarcinoma of minor salivary gland''. Even allowing for the difficulties of proper assessment of figures in reprints, there are many similarities to the microscopic appearance of our cases.…”
Section: Differential Diagnosismentioning
confidence: 99%